Model določitve kritične hitrosti ventilacije v primeru požara v cestnem predoru pri izotermnih pogojih - Donjerković, Petar (Strojniški vestnik, 2000)
This paper shows an experimental determination of the critical air velocity, characteristic for an evaluation of the efficiency of road-tunnel longitudinal ventilation in fire-incident conditions. Determination of the critical air velocity was made in isothermal conditions of a model testing of the "Sveti Rok" road-tunnel longitudinal ventilation, performed in the hydrodynamic laboratories of the Marine Research and Special Technologies Institute in Zagreb. Special attention was paid to the analysis of smoke distribution in the close vicinity of a simulated fire source for different fire loads and different longitudinal air velocities. The analysis was made by visualisation of the distribution of "cold" smoke simulated with the mixture of helium and paraffin vapours. The paper evaluates the results of an experimental determination of the critical air velocity on the scale-model with available recent results of ventilation-system field tests.
Keywords: predori cestni; sistemi prezračevalni; kritična hitrost zraka; določevanje hitrosti; cestni predori; prezračevanje; zrak; hitrost